The Effect of Accessibility and Tourist Attraction on The Decision to Visit Meikarta Central Park Mediated by Electronic Word of Mouth (E-Wom) - Dede Mulyana; Adibah Yahya; Sunita Dasman (International Journal of Economics Development Research (IJEDR), 2024)
Abstract The needs of tourists are now increasingly diverse and demand the renewal of the products provided. This is done so that tourists do not feel bored with monotonous products. One of them is in Cikarang which currently has more and more tourist attractions such as waterboom, djamoe village, saung ranggon, sehati park and one of the latest tourist attractions, namely Central Park Meikarta. This study investigates The Effect of Accessibility and Tourist Attraction on the Decision to Visit Meikarta Central Park Mediated by Electronic Word Of Mouth (E-WOM) using a quantitative approach analyzed through SmartPLS. The research examines how accessibility and tourist attraction influence visitor decisions at Meikarta Central Park, and how Electronic Word Of Mouth (E-WOM) mediates these relationships. Data were collected from visitors using questionnaires, and analysis using SmartPLS 3.0 confirmed significant direct and mediated effects. The findings underscore the importance of enhancing accessibility, improving tourist attractions, and leveraging E-WOM in attracting and retaining visitors to the park.